Long-term remote sensing monitoring on LUCC around Chaohu Lake with new information of algal bloom and flood submerging - Lin, Yi; Zhang, Tinghui; Ye, Qin; Cai, Jianqing; Wu, Chengzhao; Khirni Syed, Awase; Li, Jonathan (International journal of applied earth observation and geoinformation, 2021)
•K-ELM was utilized on spatio-temporal LUCC analysis and performed precisely.•LUCC in 23 years was demonstrated through 7 Landsat images in the Chao Lake Basin.•Frequent land cover changes have relationship with lake algae bloom pollution.•Farmland and village buildings suffered most in the flood in July 2020. Human settlements are guided by the proximity or availability of a natural resource such as river or lake basins containing set of streams. The harmonious development of human activity and natural conditions along watershed areas needs close attention and in-depth study. In this paper, the urban agglomerations and ecological spaces in the Yangtze River Delta, China, the Chao Lake Basin and its surrounding watershed ecosystem is taken as research subject for its serious environmental degradation problems during social and economic development. This paper adopted an effective machine learning algorithm (kernel-ELM) to extract land use and land /cover information, and to analyze the land use/cover pattern evolution rules of the Chao Lake Basin with long term Landsat imagery. Subsequent studies were then carried out to demonstrate the flood-affected area and its ecological impact in the basin in 2020, to reveal the occupation on land cover types. The results indicate Conclusions are drawn from the experiment results: (1) There has been significant change in cultivated land, forest land and construction land out of six key land cover types with dynamic degree of −10.17%, 4.61, 67.04% respectively. (2) Algae bloom pollution was extracted from pattern classification results and it was up to 15% of the total water area by the year 2018. (3) The occupation on land use/cover types of the flood was revealed. The results prove effective application of remote sensing technology in environmental analysis and planning for data-driven evaluation of governing policy. This work serves as a scientific basis for environmental management and regional planning in the Chao Lake Basin and can be served as a basis and a reference for evaluating an ecological policy and its impact for other economic developing watershed human settlements with ecological issues.